Trends in the epidemiology of chronic kidney disease in Russian Federation according to the Federal Diabetes Register (2013–2016) - Minara S. Shamkhalova; Olga K. Vikulova; Anna V. Zheleznyakova; Michail A. Isakov; Marina V. Shestakova; Ivan I. Dedov (Сахарный диабет)
BACKGROUND: Chronic kidney disease (CKD) is one of the most severe complications of diabetes mellitus (DM), this determines the importance of the study of epidemiological characteristics of the disease. AIMS: To assess the epidemiological characteristics of CKD in adult DM patients with type 1 (T1), 2 (T2) in Russian Federation in 2013–16. METHODS: We have used the database of the Russian Federal Diabetes register, 81st regions included in online register. Indicators were estimated per 10,000 adult DM patients (>18years). RESULTS: In 2016, the CKD frequency registration was T1 23%, T2 6.9% with marked interregional differences 1.5-49.9%, 0.6–23.5%, respectively. The CKD prevalence in dynamics 2013→2016 was 2171.4→2303.0 in T1 and 512. →687.2 in T2. The incidence of new CKD cases increased 2 times in T1 (215.5 vs 104.2), and 3.7 times in T2 (190.4 vs 51.8). The analysis of distribution by CKD stages by KDIGO indicates the increase in the proportion of patients with low and moderate cardiovascular risk and end stage renal disease (ESRD) (with the initial stages of CKD, C1/2 A1) - 12.0→46.8% in T1; 10.0→50.4% in T2. The proportion of patients with a very high risk (stages C4/5 C3aA3 and C3bA2-3) progressively decreases: 13.4→6.7% in T1, 11.3→4.4% in T2. We observed relation between the CKD prevalence and DM duration. CKD develops in 5.1% patients if T1<5 years and in 48.0% if T1>30years; in T2 3.5% and 20.3%, respectively. The average age of CKD onset in T1 increased for 4,3yr (36,1→40,2), in T2 for 2,4yr (64,4→66,8), DM duration until CKD development increased in T1 11.8→14.2yr, in T2 7.6→8.2yr. CONCLUSIONS: There is a significant improvement in the quality of CKD diagnostics at the earlier stages, older age and a longer DM duration before CKD onset in both types while we observed the increasing trends in CKD prevalence in Russian Federation in the dynamics of 2013-2016. Advances in the management of patients with DM in recent years do not reduce the risk of CKD, but give us a delay in its development. The marked interregional differences frequency of registration of CKD might indicate some remaining problems in verification in a number of regions where the standard for mandatory assessment of albuminuria and glomerular filtration rate not implemented.